Trade-offs in competitive transport operations - Usman Akbar; Akash Kumar; Hameed Khan; Muhammad Asif Khan; Khansa Parvaiz; Judit Oláh (Economies, 2020)
One of the goals of developing a transport corridor is to promote socio-economic development by improving connectivity and sustainable transport operations, which largely depends on the operational strategy. Trade-off policies can be important tools for gaining the competitive advantage of road transport corridors, and thus, help facilitate sustainable growth and welfare. This article uses a case-based approach to observe the trade-offs in the first phase of transport infrastructure development, and then, in the second stage, further explores the trade-off variables in the transport operations strategy under the China-Pakistan Economic Corridor (CPEC). The results from the three cases of the parallel route system of the CPEC indicate that trade-off is an easily understandable and applicable method, which can foresee the operational gains or compromises for significant welfare of the regions. The implications of the trade-off are two fold, first is the "importance" of the trade-off, which is related to its impact on operational competitiveness. The other is the "sensitivity" of the trade-off, in terms of the change that will be caused to one variable when changing the other. The trade-off concept can be used for several landlocked transport corridors to achieve a competitive edge in transit trade.
Keywords: 330; trade-offs; transport operations; competitiveness; sustainability